2014
DOI: 10.1002/nvsm.1515
|View full text |Cite
|
Sign up to set email alerts
|

Effect of university heritage and reputation on attitudes of prospective students

Abstract: This study examines the impact of heritage and reputation of nonprofit universities on attitudes of prospective students. Data were collected from 208 community college (preuniversity) students in the USA. Results from structural equations modeling indicate that university heritage positively impacts university reputation, potential students' attitudes, and intentions to pay a tuition premium as well as to recommend the university. Students' nationality moderates the relationships between university heritage, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 58 publications
1
25
0
2
Order By: Relevance
“…The findings of the current study indicate a significant positive correlation between MO and student satisfaction, which is consistent with the findings from previous literature concerning the increasing importance of marketing in schools (Stokes, 2002;Bock, Poole, & Joseph, 2014), the relationship between branding strategies and student recruitment (Bock et al, 2014;Chapleo, 2015), the effect of university heritage and reputation on prospective students' attitudes (Merchant et al, 2015), and the pivotal role of marketing in corporate environment (Sanzo, Santos, Vázquez, & Álvarez, 2003;Narver & Slater, 1990). It seems reasonable to assume a positive relationship between MO and student satisfaction because, similar to a business, the university attempts to implement marketing strategies in order to fulfill students' needs, wants, and aspirations, thereby improving student satisfaction.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The findings of the current study indicate a significant positive correlation between MO and student satisfaction, which is consistent with the findings from previous literature concerning the increasing importance of marketing in schools (Stokes, 2002;Bock, Poole, & Joseph, 2014), the relationship between branding strategies and student recruitment (Bock et al, 2014;Chapleo, 2015), the effect of university heritage and reputation on prospective students' attitudes (Merchant et al, 2015), and the pivotal role of marketing in corporate environment (Sanzo, Santos, Vázquez, & Álvarez, 2003;Narver & Slater, 1990). It seems reasonable to assume a positive relationship between MO and student satisfaction because, similar to a business, the university attempts to implement marketing strategies in order to fulfill students' needs, wants, and aspirations, thereby improving student satisfaction.…”
Section: Discussionsupporting
confidence: 92%
“…One of those solutions that schools can adopt is MO (Chapleo, 2015;Merchant et al, 2015). MO is a key driver of business profitability, innovation, employees' commitment, and performance of organizations (Kirca, Jayachandran, & Bearden, 2005;Noble, Sinha, & Kumar, 2002;Atuahene-Gima, 1996;Narver & Slater, 1990).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the education sector, the research found that the reputation of the college has significant influence toward the attitude of the prospective student. However, the research did not explain the exact percentage of the college influence [6]. A prior study claimed that the interest to the major has become a crucial factor in determining student's decision-making.…”
Section: Introductionmentioning
confidence: 90%
“…Simultaneously the behavioural economics gained popularity and it was applied to various fields including the education sector. A number of research was conducted on student behaviour to understand variables which impact the selection of higher education institution [6,7,8,9]. We can find certain similarities between student decision making behaviour and customer buying behaviour [10].…”
Section: Introductionmentioning
confidence: 99%